2021
DOI: 10.1002/pbc.28896
|View full text |Cite
|
Sign up to set email alerts
|

Thiotepa–melphalan myeloablative therapy for high‐risk neuroblastoma

Abstract: Background Appropriate high‐dose chemotherapy (HDC) for high‐risk neuroblastoma has not yet been established. In Japan, a unique HDC regimen that comprises two cycles of a total of 800 mg/m2 of thiotepa and a total of 280 mg/m2 of melphalan is widely utilized. Methods To evaluate the safety and efficacy of this thiotepa–melphalan high‐dose therapy for high‐risk neuroblastoma, we reviewed the medical records of 41 patients with high‐risk neuroblastoma who underwent this regimen followed by autologous peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…But, inferior EFS and OS in high-risk NB patients with MYCN amplification have been reported from the COG and other studies [ 25 , 26 , 27 , 28 ]. One study from Japan showed MYCN amplification was the most favorable prognostic factor for EFS of high-risk NB [ 29 ]. Our results showed that the patients with MYCN amplified had worse the EFS and OS rates than those without MYCN amplified in high-risk NB.…”
Section: Discussionmentioning
confidence: 99%
“…But, inferior EFS and OS in high-risk NB patients with MYCN amplification have been reported from the COG and other studies [ 25 , 26 , 27 , 28 ]. One study from Japan showed MYCN amplification was the most favorable prognostic factor for EFS of high-risk NB [ 29 ]. Our results showed that the patients with MYCN amplified had worse the EFS and OS rates than those without MYCN amplified in high-risk NB.…”
Section: Discussionmentioning
confidence: 99%
“…Cheung and colleagues raised several points in contention: OS with long follow‐up may be more indicative of cure than EFS when including post‐relapse patients; frequent testing of nontransplant patients may mean relapses are more readily detectable when localized and amenable to salvage therapies; evidence from prior decades may not be retained in the contemporary era of immunotherapy; and a high prevalence of late effects. Debate regarding the merits of transplant has continued to persist, most recently when an analysis of 41 patients who underwent ASCT using thiotepa‐melphalan at three institutions in Japan prompted Kushner to respond questioning both the study and wider evidence for continued use of ASCT in the modern era 29,30 …”
Section: Exploring the Controversiesmentioning
confidence: 99%
“…И хотя другие исследования, представленные в нашем анализе, продемонстрировали выраженное влияние ответа на индукцию на выживаемость, часть из них была ограничена небольшим объемом выборки и коротким периодом наблюдения [20,22]. В исследовании F. Yamazaki и соавт.…”
Section: таблицаunclassified
“…В исследовании F. Yamazaki и соавт. из Японии показано значительное повышение БСВ и ОВ у пациентов, достигших CR/VGPR/ PR в конце индукции, и эта разница была еще более очевидной в подгруппе пациентов с CR/VGPR против худшего ответа (5-летняя БСВ 78,6 ± 11,0% против 22,2 ± 8,0%; p = 0,00041 и 5-летняя ОВ 92,9 ± 6,9% против 37,0 ± 9,3%; p = 0,00019) [22]. Также влияние лучшего ответа на индукцию на более высокие показатели долгосрочной выживаемости сохранялась у пациентов с наличием амплификации гена MYCN при проведении подгруппового анализа.…”
Section: таблицаunclassified